Does a non-performing assets disposal fund help control systemic risk? Evidence from an interbank financial network in China - Lei Song; Yu Chen (Financial Innovation)
Abstract The COVID-19 pandemic precipitated a surge in the non-performing assets held by financial institutions, elevating systemic risk in financial networks. Therefore, developing strategies to alleviate this risk, with a focus on non-performing assets, has become a research area of interest. Supported by policies related to the Chinese insurance market, this study proposes the establishment of a non-performing assets disposal fund backed by insurance capital. This fund will invest in the non-performing assets of financial institutions with the aim of mitigating systemic risk. Using a linear threshold model, we identify an asymptotically optimal scheme for disposing of non-performing assets. Additionally, we construct a payment model integrated with non-performing assets, from which we derive an optimal payment and clearing strategy. Our research also proposes a robust set of criteria to assist regulators in determining whether to use the non-performing assets disposal fund. To demonstrate the efficacy of the fund in reducing systemic risk, we conduct simulations and analyze data from the Chinese interbank financial network. Through this rigorous analysis, we confirm the role of the fund in enhancing the stability of the financial system.